2018
DOI: 10.3892/ijo.2018.4562
|View full text |Cite|
|
Sign up to set email alerts
|

Lipocalin 2 inversely regulates TRAIL sensitivity through p38 MAPK-mediated DR5 regulation in colorectal cancer

Abstract: TNF-related apoptosis-inducing ligand (TRAIL) induces apoptosis through death receptors (DRs)4 and/or 5 expressed on the cell surface. Multiple clinical trials are underway to evaluate the antitumor activity of recombinant human TRAIL and agonistic antibodies to DR4 or DR5. However, their therapeutic potential is limited by the high frequency of cancer resistance. In this study, we provide evidence demonstrating the role of lipocalin 2 (LCN2) in the TRAIL-mediated apoptosis of human colorectal cancer (CRC). By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In this study, inhibiting LCN2 using anti-LCN2 antibody resulted in suppression of major tumor promoting signalling pathways like TNF alpha, IL17 and NFkB signalling, which ultimately resulted in tumor regression. Numerous reports suggest that all these pathways are linked to LCN2 in various human malignancies [55][56][57][58][59] . For example, in PC-3 prostate cancer cells, it has been reported that TNF alpha stimulates LCN2, thus protecting the tumor cells from apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, inhibiting LCN2 using anti-LCN2 antibody resulted in suppression of major tumor promoting signalling pathways like TNF alpha, IL17 and NFkB signalling, which ultimately resulted in tumor regression. Numerous reports suggest that all these pathways are linked to LCN2 in various human malignancies [55][56][57][58][59] . For example, in PC-3 prostate cancer cells, it has been reported that TNF alpha stimulates LCN2, thus protecting the tumor cells from apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the molecular mechanism of the formation of kidney stones, studies have shown that LCN2 may play an important role 16 . LCN2, which is also known as neutrophil gelatinase-associated LCN, is expressed in tubular cells and neutrophils and is related to cellular apoptosis and inflammation 17,18 . However, little is known about the role of LCN2 in kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the role of LCN2 in kidney stones. There are also studies that indicate that LCN2 can be regulated and that it is associated with many signalling pathways in certain tumour cell models [10][11][12][13][14][15][16][17][18][19] . However, little is known about the specific regulation of LCN2 and the role of LCN2 and related signalling pathways in kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…LCN2 is involved in TNF-related apoptosis-inducing ligand (TRAIL)-mediated apoptosis in CRC. The mRNA expression data for 71 CRC tissues have revealed that the expression of TRAIL-R2 is inversely related to LCN2 and LCN2 knockdown in CRC cells, which increases the sensitivity to TRAIL via p38 MAPK/CHOP-induced upregulation of TRAIL-R2 [138].…”
Section: Lipocalinmentioning
confidence: 99%